Differentiating bulk nanobubbles from nanodroplets and nanoparticles. (June 2021) - Eklund, Fredrik; Alheshibri, Muidh; Swenson, Jan
Abstract: History has shown that it is not as easy as one might think to differentiate between bulk nanobubbles and nanodroplets or nanoparticles. It is generally easy to detect colloids (i.e. something that looks different, e.g. scatters light differently than its surrounding solvent), but less easy to determine the nature of these colloids. This has led to misinterpretations in the literature, where nanodroplets or nanoparticles have mistakenly been assumed to be nanobubbles. In this paper, we review a multitude of experimental methods and approaches to prove the existence of bulk nanobubbles. We conclude that combinations of optical detection with physical perturbations such as pressure or ultrasound, or phase-sensitive holographic methods are the most promising and convenient approaches. Graphical abstract: Image 1